The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4314/wsa.v36i5.61996
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of non-essential trace metals in tissues and organs of <i>Clarias gariepinus</i> (sharptooth catfish) from the Vaal River system – strontium, aluminium, lead and nickel

Abstract: This is the first paper reporting on results obtained in a metal bioaccumulation study in the Vaal River system. It discusses concentrations of four non-essential elements (strontium, aluminium, lead and nickel) in water, sediment and various fish tissues. A second paper will report on concentration levels of the remaining five essential trace metals (chrome, copper, iron, manganese and zinc) studied. While heavy metals did accumulate in C. gariepinus tissues, no clear trends emerged with regard to differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 115 publications
(80 reference statements)
3
14
4
Order By: Relevance
“…This is further evident in the BCF values determined in Table 5, as the liver, kidney and gill tissues had many BCF values greater than 1. Similar trends have been observed in previous studies conducted on fishes from the Vaal Dam reservoir, in which the gills, kidney and liver possess the highest element concentrations of the tissues studied (Retief et al, 2006;2009;Crafford and Avenant-Oldewage, 2010;2011;Gilbert and AvenantOldewage, 2014). Functioning as the primary detoxification organ, the liver performs crucial roles in blood filtration and toxicant removal (Wood, 2012).…”
Section: Fish Tissue Concentrationssupporting
confidence: 88%
“…This is further evident in the BCF values determined in Table 5, as the liver, kidney and gill tissues had many BCF values greater than 1. Similar trends have been observed in previous studies conducted on fishes from the Vaal Dam reservoir, in which the gills, kidney and liver possess the highest element concentrations of the tissues studied (Retief et al, 2006;2009;Crafford and Avenant-Oldewage, 2010;2011;Gilbert and AvenantOldewage, 2014). Functioning as the primary detoxification organ, the liver performs crucial roles in blood filtration and toxicant removal (Wood, 2012).…”
Section: Fish Tissue Concentrationssupporting
confidence: 88%
“…This is probably an artefact of the larger fish being captured at the impoundment with higher metal concentrations in fish muscle tissue, rather than its being biologically significant. Fish age, size, sex, life stage, fish behaviour and orientation to the sediment may play a significant role with regard to metal accumulation (Kidwell et al 1995;Crafford and Avenant-Oldewage 2010). However, the present study found no correlation between the patterns of metal concentrations in the fish muscle tissue and those of the water and sediment.…”
Section: Metal Concentrations In Fish Muscle Tissuecontrasting
confidence: 71%
“…However, the present study found no correlation between the patterns of metal concentrations in the fish muscle tissue and those of the water and sediment. In addition to biological variables, physical and chemical parameters such as pH, dissolved oxygen, water hardness, salinity, alkalinity and the presence of other metals may also play a role with regard to the bioavailability of metals to fish (Palaniappan and Karthikeyan 2009;Crafford and Avenant-Oldewage 2010). It is possible that the measurement of available metals, particularly in the sediment, may not be representative of the actual bioavailability of these metals.…”
Section: Metal Concentrations In Fish Muscle Tissuementioning
confidence: 95%
“…The majority of the nestling osprey we tested in the rivers of the Coastal Plain nested on fresh water. Due to their feeding behavior and trophic position, catfish are known to accumulate lead (Crafford and Avenant-Oldewage 2010). Earlier work has shown that the lead in nestling osprey in the Chesapeake Bay region is ingested, not inhaled .…”
Section: Spatial and Demographic Patterns Of Lead Exposurementioning
confidence: 99%